Occupational exposure to pesticides and health symptoms among family farmers in Brazil - Buralli, Rafael Junqueira; Ribeiro, Helena; Iglesias, Verónica; Muñoz-Quezada, María Teresa; Leão, Renata Spolti; Marques, Rejane Correa; Almeida, Milena Maria Cordeiro de; Guimarães, Jean Remy Davée (Revista de Saúde Pública, 2020)
OBJECTIVE: To explore the association of occupational pesticide exposure with acute and mental health symptoms. METHODS: Cross-sectional survey carried out with 78 Brazilian family farmers, who were pesticide applicators and helpers conveniently selected. Symptoms and exposure data were collected by interviews, and mental health outcomes by the Self-Reporting Questionnaire. Blood samples were analyzed to assess cholinesterase levels. Exposure indicators and symptoms were compared between applicators and helpers, and Poisson regression was performed to estimate prevalence ratios. RESULTS: Farmers reported exposure to multiple pesticides from early ages; they worked without safety training, technical support, and full protective equipment, and they had a high prevalence of acute and mental health symptoms (e.g., headache, mucosal irritation, tachycardia, and depressive signs). Applicators had more cholinesterase changes than helpers, but less symptoms. Helpers used less personal protection and had significantly higher prevalence ratio of headache, dyspnea, wheezing, cough, poor digestion, tiredness, and feeling worthless, after adjustment. CONCLUSIONS: Acute and mental health symptoms were observed, both among farmers and helpers. Thus, surveillance actions must be reinforced in Brazil, technical support and safety training improved, focused on applicators and helpers, who are occupationally and environmentally exposed to pesticides. Agricultural practices of these groups with less pesticide use should receive incentive.